Designing Quasi-Experimental Impact Studies of Agricultural Research at Scale - Meenakshi, J.V.; Johnson, Nancy; Karasalo, Mina (CGIAR Advisory Services, 2021)
Providing credible and quantifiable measures of the impact of CGIAR innovations at scale has always been a challenge. Recent SPIA-supported research has attempted to address this challenge using quasi-experimental approaches to assessing impact. This technical note details some of these completed and ongoing studies and approaches, focusing on the identification strategies used to infer causal impact, and the kinds of diverse data sets that may be brought to bear in making these inferences. A key message is also to integrate impact evaluation designs as part and parcel of monitoring and evaluation efforts.